Clinicobiochemical and pathological correlation in alcoholic liver disease among Indian patients - Chowdhury, Atanu Roy; Brahmachari, Ramkrishna; Saha, Soumyojit (International Journal of Research in Medical Sciences, 2021)
Background: Alcohol is one of the leading causes of “preventable” morbidity and mortality worldwide. It is associated with liver damage. A gray area is temporal relation between clinico-biochemical severity and histological changes in liver, neither this issue has been widely studied. Methods: A hospital based cross sectional clinico-pathological pilot study was undertaken in a tertiary care hospital in West Bengal in patients with a history of alcohol intake who had been admitted in the inpatient department of medicine. Assessment of patients with history of alcohol intake with respect to clinical, biochemical and histopathological examination was performed. The correlation between clinico-biochemical severity and histopathological stages in cases of alcoholic liver disease was evaluated. Results: There was a significant correlation between clinico-biochemical severity and liver biopsy changes. The severity of histopathological changes of alcoholic liver disease was found to correlate significantly with the severity of abdominal parameters with Pearson correlation cofactor of 0.819. Conclusions: Both the clinic-biochemical severity and histological changes had no correlation with the duration of alcohol intake in contrast to earlier studies which had demonstrated a definite correlation of alcoholic liver disease (ALD) with both the amount and duration of alcohol intake. Larger studies will be required to substantiate the findings of this study.